Comprehensive evaluation of plasma microbial cell-free DNA sequencing for predicting bloodstream and local infections in clinical practice: a multicenter retrospective study - Pang, Feng; Xu, Wenbin; Zhao, Hui; Chen, Shuai; Tian, Yaxian; Fu, Juanjuan; You, Zhiqing; Song, Pingping; Xian, Qingjie; Zhao, Qigang; Wang, Chengtan; Jia, Xiuqin (Frontiers in Cellular and Infection Microbiology, 2024)
Background Metagenomic next-generation sequencing (mNGS) of plasma cell-free DNA (cfDNA) shows promising application for complicated infections that cannot be resolved by conventional microbiological tests (CMTs). The criteria for cfDNA sequencing are currently in need of agreement and standardization. Methods We performed a retrospective cohort observation of 653 patients who underwent plasma cfDNA mNGS, including 431 with suspected bloodstream infections (BSI) and 222 with other suspected systemic infections. Plasma mNGS and CMTs were performed simultaneously in clinical practice. The diagnostic efficacy of plasma mNGS and CMTs in the diagnosis of blood-borne and other systemic infections was evaluated using receiver operating characteristic (ROC) curves. The sensitivity and specificity of the two methods were analyzed based on the final clinical outcome as the gold standard. Results The mNGS test showed an overall positive rate of 72.3% (472/653) for detecting microorganisms in plasma cfDNA, with a range of 2 to 6 different microorganisms detected in 171 patient specimens. Patients with positive mNGS results were more immunocompromised and had a higher incidence of severe disease (P<0·05). The sensitivity of mNGS was higher for BSI (93·5%) and other systemic infections (83·6%) compared to CMTs (37·7% and 14·3%, respectively). The mNGS detected DNA from a total of 735 microorganisms, with the number of microbial DNA reads ranging from 3 to 57,969, and a higher number of reads being associated with clinical infections (P<0·05). Of the 472 patients with positive mNGS results, clinical management was positively affected in 203 (43%) cases. Negative mNGS results led to a modified clinical management regimen in 92 patients (14.1%). The study also developed a bacterial and fungal library for plasma mNGS and obtained comparisons of turnaround times and detailed processing procedures for rare pathogens. Conclusion Our study evaluates the clinical use and analytic approaches of mNGS in predicting bloodstream and local infections in clinical practice. Our results suggest that mNGS has higher positive predictive values (PPVs) for BSI and systemic infections compared to CMTs, and can positively affect clinical management in a significant number of patients. The standardized whole-process management procedure for plasma mNGS developed in this study will ensure improved pre-screening probabilities and yield clinically valuable data.